KEBIJAKAN FISKAL DAN MONETER DALAM PERSPEKTIF EKONOMI ISLAM - Al-Fadli Al-Fadli (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2015)
Islam does not separate between what is required for people with efforts to achieve human prosperity, but it makes two things are related. Muslims consider the interests of individual communities simultaneously. When Islam organize a society problem, it noticed the interests of individuals, thus in vise versa when setting individual interests, community interests are not ignored. This paper outlines a sistematic way how the rules of Islam are in the economy macro, especially in matters of monetary policy and physical (monetary and fiscal policy). However, before entering into the study of monetary policy in Islam economy, it should be emphasized that Islam forbids the practice of usury. Fiscal policy is government policy to use instruments such as tax-fiscal instruments (tax), transfer, or government spending (government spending / purchase) intended to affect the macro-economic indicators such as economic growth and inflation. In general, fiscal policy is a form of macro-economic policies in government where the achievement of objectives focused on goods within the country (domestic goods), household, and corporate / private / entrepreneur. Monetary policy (monetary policy) is an effort to control macroeconomic circumstances in order to be able to run as desired by setting the amount of money circulating in the economy. That effort aims tomakeprice stability and inflation Islam tidak memisahkan antara apa yang wajib bagi masyarakat dengan upaya mewujudkan kesejahteraan manusia, tapi menjadikannya dua hal yang berhubungan. Islam memperhatikan kepentingan individu dan masyarakat secara bersamaan. Ketika Islam mengatur masalah masyarakat, ia memperhatikan kepentingan individu, demikian sebliknya ketika mengatur kepentingan individu, kepentingan masyarakat tidak diabaikan.Tulisan ini menguraikan secara sistematis bagaimana aturan-aturan ekonomi Islam secara makro itu, khususnya dalam masalah kebijakan moneter dan fiskal ( monetary dan fiskal policy). Kebijakan fiskal adalah kebijakan pemerintah dengan menggunakan instrument-instrument fiskal seperti pajak (tax), transfer, atau belanja pemerintah (government spending/purchase) yang ditujukan untuk mempengaruhi indikatorindikator makro ekonomi seperti pertumbuhan ekonomi dan inflasi.Secara umum, kebijakan fiskal adalah bentuk kebijakan ekonomi makro dalam pmerintah di mana pencapaian sasarannya difokuskan pada barang-barang di dalam negeri (domesticgoods), rumah tangga, ataupun perusahaan/swasta/pengusaha. Kebijakan moneter (monetarypolicy) adalah suatu usaha dalam mengendlikan keadaan ekonomi makro agar dapat berjalan sesuai dengan yang diinginkan melalui pengaturan jumlah uang yang beredar dalam perekonomian. Usaha tersebut dilakukan agar terjadi kestabilan harga dan inflasi.